Nunca más : informe de la Comisión Nacional sobre la Desaparición de Personas. (Eudeba, Editorial Universitaria de Buenos Aires, 2011)
"Report of the Argentinian National Commission on the Disappearance of Persons. "The commission has presided over hearings of thousands of cases of abduction, disappearance, torture, and executions. Every individual case was documented in a numbered file. It compiled over 50,000 pages of documentation. A shocking summary was published as an official report in Spanish in 1984. Faced with the thousands of testimonies and horrific facts the commission concluded with a set of recomendations to pursue legal action against the responsible. The report of the commission was published in English with an introduction by Ronald Dworkin, as a book under the name Nunca Mas (Never Again), published by Farrar Straus Giroux, New York. Also published in London by Faber and Faber Ltd, 1986. ISBN 0374223505. While the report explicitly states that the documented cases are by no means exhaustive, and that many cases were most probably left unreported, till this date, this report is the most extensive document available publicly."